CONSUMO DE NÁUPLIOS DE ARTÊMIA POR LARVAS DE LAMBARI EM DIFERENTES IDADES - TAVARES, Tainara Vieira; CAVALCANTI, Leandro Borges; CAITANO, Welison Aparecido Bispo; SANTOS, Jussara Garrido; FERRAZ, André Luiz Julien; COSTA, Deliane Cristina (ANAIS DO ENIC, 2025)
-